2017
DOI: 10.1080/21691401.2017.1345929
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of hepatogenic differentiation of iPS cells on an aligned polyethersulfone compared to random nanofibers

Abstract: The application of stem cells holds great promises in cell and tissue transplants. This study was designed to compare the hepatogenic differentiation of iPSCs on aligned PES/COL versus random. Aligned and random PES/COL nanofibrus scaffolds were fabricated by electrospining and their surface modified through plasma treatment and collagen coating. The scaffolds were characterized using scanning electron microscopy (SEM) and ATR-FTIR. Morphology and biochemical activities of the differentiated hepatocyte-like ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 28 publications
4
24
0
Order By: Relevance
“…We found that (a) PLLA/PCL polymer supports the attachment, proliferation, and differentiation of hiPSCs; (b) the successful generation of hepatic‐like cells from hiPSCs on the hybrid scaffold; and (c) the newly derived cells expressed higher levels of liver markers than cells differentiated on gelatin‐coated plates and single nanofibrous scaffolds. Our results are consistent with those of Mahmoodinia Maymand et al (), in using SEM, we found that the formed cells aggregated, adhered, and penetrated to the scaffold. Our SEM results showed a highly porous and nonwoven architecture that mimics ECM structure, likewise Kinasiewicz et al ().…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that (a) PLLA/PCL polymer supports the attachment, proliferation, and differentiation of hiPSCs; (b) the successful generation of hepatic‐like cells from hiPSCs on the hybrid scaffold; and (c) the newly derived cells expressed higher levels of liver markers than cells differentiated on gelatin‐coated plates and single nanofibrous scaffolds. Our results are consistent with those of Mahmoodinia Maymand et al (), in using SEM, we found that the formed cells aggregated, adhered, and penetrated to the scaffold. Our SEM results showed a highly porous and nonwoven architecture that mimics ECM structure, likewise Kinasiewicz et al ().…”
Section: Discussionsupporting
confidence: 93%
“…Preliminary studies have used various scaffolds such as PES (Hashemi et al, ; Kazemnejad et al, ), PLLA (Feng et al, ; Ghaedi et al, ), and PCL/collagen/PES (Mahmoodinia Maymand et al, ) for hepatocyte differentiation. In the current study, our results demonstrated that hepatic markers are markedly expressed better in hybrid scaffolds than single nanofibrous scaffolds (Mahmoodinia Maymand et al, ). l ‐Form of poly‐lactic acid is a polyester approved by Food and Drug Administration and l ‐lactic acid is the product of this scaffolds degradation, which is harmless for the body (Islami, Mortazavi, Soleimani, & Nadri, ).…”
Section: Discussionsupporting
confidence: 58%
“…14,26,43 To investigate the effect of DWJS on hiPSCs during hepatic differentiation, hiPSCs were cultured on DWJS or in TCPs with same hepatic induction medium after which cell morphology and expression of specific hepatic markers were examined. 14,26,43 To investigate the effect of DWJS on hiPSCs during hepatic differentiation, hiPSCs were cultured on DWJS or in TCPs with same hepatic induction medium after which cell morphology and expression of specific hepatic markers were examined.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Using xenogeneic primary hepatocyte and immortalized hepatocellular carcinoma cell lines are also associated with some problems, including immunogenicity, pathogenicity, and tumorgenesis. 23,[25][26][27] Recently, decellularized scaffold of heart and lung were repopulated with human iPSC-derived organ specific cells. Due to the unlimited selfrenewing capacity and less immunogenicity of iPSCs, they became a preferred choice for hepatocyte generation.…”
mentioning
confidence: 99%
“…Up to recent years, the IPCs differentiation of hADSCs has mostly been performed in 2D culture and fully functional and mature islet‐like clusters maintaining their features in the condition of 3D culture have not been developed. In addition, natural and polymeric synthetic scaffolds provide a suitable substrate and surface area for cell seeding and attachment as well as developing and improving stem cell proliferation and differentiation capability (Amer, Mahoney, & Bryant, ; Mahmoodinia et al, ). The combination of hADSCs with nanofibrous scaffolds has many useful effects including the slow diffusion of growth factors and metabolites, as well as the fabrication of pancreas architecture for pancreas tissue engineering purposes in the future (Javad et al, ).…”
Section: Discussionmentioning
confidence: 99%